Nutrition for power sports: Middle-distance running, track cycling, rowing, canoeing/kayaking, and swimming - Stellingwerff, T.; Maughan, R. J.; Burke, L. M. (Journal of Sports Sciences, 2011)
Contemporary training for power sports involves diverse routines that place a wide array of physiological demands on the athlete. This requires a multi-faceted nutritional strategy to support both general training needs - tailored to specific training phases - as well as the acute demands of competition. Elite power sport athletes have high training intensities and volumes for most of the training season, so energy intake must be sufficient to support recovery and adaptation. Low pre-exercise muscle glycogen reduces high-intensity performance, so daily carbohydrate intake must be emphasized throughout training and competition phases. There is strong evidence to suggest that the timing, type, and amount of protein intake influence post-exercise recovery and adaptation. Most power sports feature demanding competition schedules, which require aggressive nutritional recovery strategies to optimize muscle glycogen resynthesis. Various power sports have different optimum body compositions and body weight requirements, but increasing the power-to-weight ratio during the championship season can lead to significant performance benefits for most athletes. Both intra- and extracellular buffering agents may enhance performance, but more research is needed to examine the potential long-term impact of buffering agents on training adaptation. Interactions between training, desired physiological adaptations, competition, and nutrition require an individual approach and should be continuously adjusted and adapted.